Washington's Government: Charting the Origins of the Federal Administration - Edling, Max; Kastor, Peter J; Brown, Kate E; Chervinsky, Lindsay M; Fagal, Andrew J. B; Hulsebosch, Daniel J; Rao, Gautham; Rockwell, Stephen J; Zagarri, Rosemarie (Early American Histories, 2021)
Washington's Government shows how George Washington's administration the subject of remarkably little previous study was both more dynamic and more uncertain than previously thought. Rather than simply following a blueprint laid out by the Constitution, Washington and his advisors constructed over time a series of possible mechanisms for doing the nation's business. The results were successful in some cases, disastrous in others. Yet at the end of Washington's second term, there was no denying that the federal government had achieved remarkable results. As Americans debate the nature of good national governance two and a half centuries after the founding, this volume's insights appear timelier than ever.